Strategi Optimalisasi Penggunaan Layanan Mobile Banking Pada PT. Bank Sumut Syariah KCP. Stabat - Ispandi Manurung; Muhammad Saleh; Anjur Perkasa Alam (Al-Sharf: Jurnal Ekonomi Islam, 2023)
This study aims to determine the strategy of the north sumatra bank in optimizing mobile banking services at PT. Bank Sumut Syariah Stabat. This type of research is descriptive research using qualitative methods. The research data is sourced from primary data and secondary data. Data collection techniques in this study used observation, interview and documentation methods. The results of this study show that the strategy of sharia banks in optimizing mobile banking services through several ways and stages, one of which is by issuing an application called "SUMUT Mobile". The launch of this application aims to make customers of sharia sumut banks not bored and always comfortable in making transactions on mobile banking services This application can be accessed through the Android Smartphone application. In this application, there are many features such as fund transfers, balance checks, electricity token payments, credit purchases and so on which will certainly make it easier for users to make transactions.